Effect of light type and mechanical scarification on the germination of passion fruit seeds (Passiflora edulis var. flavicarpa) - ALVA-OBREGÓN , Denfiger Manuel (2025)
The physiological quality of seeds is essential for ensuring efficient agricultural production. This study evaluated the interaction between light type (LED, fluorescent, darkness) and mechanical scarification on seed germination and viability. A completely randomized design (CRD) with a 3 × 2 factorial arrangement assessed six treatments involving scarified and non-scarified seeds. Seeds collected from three locations were dried, pretreated with tap water to overcome dormancy, and evaluated using the Between-Paper Method (BP) in light chambers with 100 seeds per replication. A 1 % tetrazolium viability test was conducted on scarified seeds, incubated at 30 °C for 18 hours to confirm embryo viability. Germination percentages were calculated based on the number of normal seedlings per treatment. Statistical analysis revealed a significant interaction between light type and micropyle scarification (p < 0.05), demonstrating that the effect of scarification depends on the light conditions. Scarified seeds exposed to LED light achieved the highest germination percentage (93.5 %), while non-scarified seeds subjected to fluorescent light or darkness showed the lowest rates. Micropyle scarification significantly improved germination (66.5 % versus 44.08 % for non-scarified seeds). No direct correlation was found between germination and viability (r = -0.88), highlighting the influence of additional factors. Furthermore, seeds from the Zapallal bio-garden showed superior germination, likely due to favorable local conditions. These results confirm that Passiflora edulis var. flavicarpa seeds are positively photoblastic,